REPRESENTASI, RELASI, DAN IDENTITAS UNDANG-UNDANG LAUT: KAJIAN EKOLINGUISTIK KRITIS - Fauzi, Mohd; Hermansyah, Hermansyah (Universitas Lancang Kuning, 2021)
This study aims to reveal the representation, relations, and identity of the Maritime Laws using a critical ecolinguistic approach. This linguistic phenomenon is a treasure trove of Malay intellectual property in the past. This type of research is literature research with a qualitative descriptive method. The data was collected by using the method of observing free and speaking with observation and note-taking techniques. The data analysis used the mix and match methods, especially referential equivalents, translational equivalents, and pragmatic equivalents. The results of data analysis were explained using informal methods. The data used is written data from the Malay Maritime Laws. The results have shown that the contents of the text of the Malay Maritime Laws are related to the duties and obligations of seafarers who sail. Ecolexicons, phrases, and sentences related to marine and shipping existed at that time. This fact occurs because the sea has been the lifeblood of the Malay people for centuries and will continue to be passed on to future generations.